Universal Salt Iodisation: Lessons learned from Cambodia for ensuring programme sustainability. (24th August 2020) - Codling, Karen; Laillou, Arnaud; Rudert, Christiane; Borath, Mam; Gorstein, Jonathan
Abstract: Iodine deficiency is the leading cause of preventable intellectual disability in the world, but it has been successfully prevented in most countries through universal salt iodization (USI). In 2011, Cambodia appeared to be an example of this success story, but today, Cambodian women and children are once again iodine deficient. In 2011, Cambodia demonstrated high‐household coverage of adequately iodized salt and had achieved virtual elimination of iodine deficiency in school‐age children. However, this achievement was not sustained because the USI programme was dependent on external funding, and the national government and salt industries had not institutionalized their implementation responsibilities. Recent programmatic efforts, in particular the establishment of a regulatory monitoring and enforcement system, are turning the situation around. Although Cambodia has not yet fully regained the achievements of 2011 (only 55% of tested salt was adequately iodized in 2017 compared with 67% in 2011), the recent steps taken by the government and the salt industry point to greater sustainability of the USI programme and the long‐term prevention of iodine deficiency in children, women, and the general population.